68Ga - FAPI PET/CT Unmasks Extensive Metastatic Invasive Lobular Breast Cancer when Conventional Imaging Falls Short - Sharjeel Usmani,; Khulood Al Riyami,; Anjali Jain,; Badriya Al-Qassabi,; Marwa Mamdouh Youssef, (Journal of the Pakistan Medical Association, 2026)
Invasive lobular carcinoma (ILC) is the second most common breast carcinoma, accounting for 10% to 15% of invasive breast carcinomas. ILC is more difficult to diagnose on breast imaging including mammography, ultrasound, and MRI. We report a case of 39 year old female with newly diagnosed left breast ILC (ER+, PR+, HER2). Mammography revealed a single irregular dense mass in the upper central quadrant. Conventional bone scintigraphy demonstrated no evidence of skeletal metastases. However, whole-body 68Ga FAPI PET/CT revealed a markedly different disease burden. This case highlights the added diagnostic value of 68Ga FAPI PET/CT in detecting the true extent of ILC, particularly when conventional imaging appears limited. Keywords: Lobular breast cancer; 68Ga-FAPI PET/CT; Fibroblast activation protein; cancer-associated fibroblasts; FAPI PET/CT; breast cancer